Insecure adult attachment and reflective functioning as mechanisms of the relationship between traumatic life events and suicidal ideation: A path analysis - Musetti, Alessandro; Pingani, Luca; Zagaria, Andrea; Uberti, Daniele; Meli, Salvatore; Lenzo, Vittorio; Gori, Alessio; Franceschini, Christian; Galeazzi, Gian Maria (Frontiers in Psychology, 2022)
The relationship between traumatic life events and increased suicide risk has been well reported in literature. However, the complex nature of suicidality phenomena still hinders our ability to comprehend the mediation mechanism underlying this association. In this study, we examined the mediating role of adult attachment and reflective functioning in the relationship between traumatic life events and suicidal ideation. Nine hundred and fifty Italian adults completed an online survey evaluating traumatic life events, adult attachment, reflective functioning and suicidal ideation. The path analysis showed that the positive relationship between traumatic life events and suicidal ideation was partially mediated by attachment anxiety and reflective functioning. From a clinical point of view, these results support the relevance of evaluating and improving patients’ ability to mentalize as a part of psychotherapeutic intervention aimed at reducing suicidality in people with a history of traumatic experiences and attachment anxiety.